GERNING VILLAGE ANDROID-BASED INFORMATION SYSTEM TO IMPROVE VILLAGE SERVICES AND POTENTIAL - Pebri Setiawan (STMIK Pringsewu Lampung, 2022)
The information system is a system that is used for data processing in an organization with grouping procedures and processing to become useful information for users. Android is an operating system based on the Linux kernel which is specifically intended for mobile phone devices with touchscreen features. Seeing today's technological developments brings progress in several fields such as government, education, trade, economics, business, and so on. The current development of the village cannot be separated from the development of information technology to advance the potential of every town in the territory of Indonesia. The android-based information system makes it very easy for the community to find out potential information in their village and improve the quality of community services and the potential of the government in Gerning Village so that they can provide examples of other villages to use village information system services by following current technological developments. Making this Android-based Information System was created and designed using the method of observation, interviews, and the Development Life Cycle System (SDLC) which was carried out with the Planning Stage, Analysis Stage, Stages of Design, Stages of implementation, and Stages of maintenance. To know the flow of Information Systems using the Fishbone Framework and context diagrams. The design of making this Gerning Village Android-Based Information System using the PHP and MySQL programming languages. and by testing several systems that have been implemented can run or not. This Gerning Village Android-based Information System is expected to make it easier for the public to find the information provided.